A model to align the organizational culture to lean - Mehrsa Taherimashhadi; Imma Ribas (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: Since the emergence of Lean Manufacturing many organizations strived to implement it. Nonetheless, sustainable Lean transformation is not as easy as to be simply achieved. Several aspects need to be taken into account before Lean implementation which national and organizational culture are important. By considering influences of national culture on the organizational culture, this paper aims at proposing an evaluation model to determine the cultural weaknesses of an organization and give some recommendations to manage people before implementing Lean. Design/methodology/approach: This research has been conducted based on literature review survey and semi-structured interviews. Research papers, conference proceedings, books, and official websites regarding Lean philosophy were reviewed to find the influence of national culture in Lean implementation. Different databases were scrutinized, from 2015 to 2017, containing Scopus and Web of Science with the time period of 1996-2016. A set of key terms and their combinations were used including: Toyota Production system, Lean production, Lean manufacturing, Lean management, Transformation, Implementation, Barriers/ Impediments/Challenges/Difficulties, Human resources, Success factors, Organizational culture, and National culture. Findings: The proposed evaluation model is a guide for organizations to determine cultural misalignments between the corporate culture and the Lean culture before its implementation and gives some managerial recommendations to correct them. Originality/value: This study is the first attempt to integrate the national models with Lean culture to provide an evaluation model and some recommendations to help the organization to align its culture to Lean culture before its implementation.
Keywords: 650; lean manufacturing; Toyota production system; organizational culture; national culture; lean implementation